Mixed convection of Al2O3-water nanofluid in a lid-driven cavity having two porous layers - Astanina, Marina S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2018)
In this study, mixed convection of Al2O3-water nanofluid in a lid-driven cavity under the effect of two porous layers is numerically studied. Porous layers of different thermal properties, permeability and porosity are located on the bottom wall. This bottom wall of the cavity is kept at hot temperature T-h, while upper moved wall is kept at constant cold temperature T-c and other walls of the cavity are supposed to be adiabatic. Governing equations with corresponding boundary conditions formulated in dimensionless stream function and vorticity using Brinkman-extended Darcy model for porous layers have been solved numerically using finite difference method. Numerical analysis has been carried out for a wide range of the Richardson number (Ri = 0.01-10.0), the Darcy number for the porous layer I (Da(1) =10(-7)-10(-3)), porous layers thickness (delta = 0.1-0.3) and nanoparticles volume fraction (phi = 0-0.04). It has been found that in the natural convection regime an addition of nanoparticles leads to the heat transfer enhancement, while for mixed convection and forced convection regimes an increase in nanoparticles volume fraction leads to the heat transfer reduction. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Mixed convection; Lid-driven cavity; Porous layers; Nanofluid; Numerical results